Cadeias produtivas globais e a responsabilização do poder econômico relevante por violações trabalhistas : uma análise da contribuição de Luigi Ferrajoli para o tema - Souza, Marina Hinobu de (2022)
The main objective of this research is to study Luigi Ferrajoli's theory, especially his proposal for a constitutionalism beyond the State, as an alternative to guaranteeing human and labor rights and for the effective accountability of agents who violate these rights, in the context of global supply chains. In order to do so, in the first chapter, the main problems regarding accountability for violations that occur within the production chains will be introduced, especially those related to the need to find a basis of substantive and procedural law for this purpose. Also, in this chapter, an analysis of Brazilian and international cases related to the topic will be carried out. In the second chapter, the contours of the relevant economic power will be delimited, which are those that identify the main agents and beneficiaries of violations of workers' rights in productive chains, as well as the difficulties in holding them accountable. Furthermore, this chapter will also deal with the first attempts to regulate the issue at an international level, and understand the reasons why all of them have failed so far. In this context, the third chapter will address Luigi Ferrajoli's proposal as an alternative to the problem, as it proposes, in summary, the creation of supranational institutions responsible for guaranteeing and fulfilling fundamental rights, a category derived from human rights, among which are included labor rights that are not observed in a production chain. In addition, it will be discussed about its implementation, the paths for the viability of global constitutionalism, and how it can contribute to an effective accountability of the relevant economic power in the scope of labor relations. In order to carry out this work, bibliographic and documental research techniques were used. The approach method is the deductive.